Fermentation Processes, Benefits and Risks - Laranjo, Marta (IntechOpen, 2021)
This book covers a variety of topics in the field of fermentation processes. With evolving technology and increasing knowledge regarding the benefits and risks of distinct fermentation processes, new information is available on diverse topics in this broad field. Chapters present information on industrial applications of different fermentation processes and different aspects of fermented foods such as milk, cheese, coffee, and many others. The book compiles current, expert information useful to both students and researchers.